Skin Injuries and Chlorhexidine Gluconate-Based Antisepsis in Early Premature Infants: A Case Report and Review of the Literature. Issue 4 (October 2018) - Vanzi, Valentina; Pitaro, Rosanna
Abstract : Early premature infants are subjected to many invasive procedures in neonatal intensive care units, and effective skin antisepsis is an essential step in caring for these vulnerable patients. Nevertheless, preterm infants have an anatomically and physiologically immature skin and preserving their skin integrity is essential to avoid the risk of local and systemic complications. Skin particularities of newborns reduce the list of available antiseptics in neonatology. Chlorhexidine gluconate (CHG) has excellent antiseptic properties and its antimicrobial efficacy cannot be understated, but there is great concern about its use for premature infants, referring to the risk of development skin injuries, such as skin erythema, burns, and blisters. Current guidelines do not recommend the use of CHG as antiseptic in the neonatal population, but despite the lack of safety data in premature infants, CHG is commonly used worldwide for off-label indications in neonatal intensive care units. A clinical case of an infant born at 26 weeks of gestation who sustained a CHG-related chemical burn after skin antisepsis was reported. A review of the literature was undertaken to evaluate the skin safety of CHG in infants born less than 32 weeks of gestation, to summarize clinical practice' recommendations, and to discuss the wound treatment options available.